(untitled) (Al-Qamar, 2020)
Religion is the other name of faith to which all the responsibilities are related. It is an inevitable power that plays an important role in rectifying our action. Religion is a force to be believed in and by trusting in it. Life is lived according to its order and purpose religion is not the name of particular faith. There are many religion in the world which are different to each other when we dis cuss general concept of religion we should not mix them each other. When we talk about Islam, we should avoid associate many wrong concepts to Islam without research. According to Islam “my prayers, all my act of worship, my living, my dying, all for the Lord of the worlds who has no partner, and this order has been given to me and I am the first to obey Him”. Goodness and badness in food, drink and clothing are under religion and the tendencies are beneficial which grow under religion. Religion has given us the concept of punishment and reward. Science is a method of research by which we start from a known facts and events. Ultimately, we make a faith or hypothesis that some facts are existing. This means is un biased. On other side Science is research and exploration. This mean of research is flawed and deficient. Achievements in scientific knowledge and disciplines show that no single man can remember the whole knowledge alone, for science education it is necessary to exclude all unnecessary topics and details in it. Science education should aim at prevention of evil and search of virtue. It seems that science or science education has no connection to ethics, Moreover, the religion of Islam is a religion in which the teaching of ethics is also found and it helps in the teaching of science.